How Did Employee Ownership Firms Weather the Last Two Recessions? : Employee Ownership, Emplloyment Stability, and Firm Survival - Kurtulus, Fidan Ana (Book collections on Project MUSE., 2016)
The authors examine how emplolyee ownership firms survived - compared to other firms - the last two recessions.